A new genome scan for primary nonsyndromic vesicoureteric reflux emphasizes high genetic heterogeneity and shows linkage and association with various genes already implicated in urinary tract development. Issue 1 (7th July 2013) - Darlow, J. M.; Dobson, M. G.; Darlay, R.; Molony, C. M.; Hunziker, M.; Green, A. J.; Cordell, H. J.; Puri, P.; Barton, D. E.
Abstract Primary vesicoureteric reflux (VUR), the retrograde flow of urine from the bladder toward the kidneys, results from a developmental anomaly of the vesicoureteric valve mechanism, and is often associated with other urinary tract anomalies. It is the most common urological problem in children, with an estimated prevalence of 1–2%, and is a major cause of hypertension in childhood and of renal failure in childhood or adult life. We present the results of a genetic linkage and association scan using 900, 000 markers. Our linkage results show a large number of suggestive linkage peaks, with different results in two groups of families, suggesting that VUR is even more genetically heterogeneous than previously imagined. The only marker achieving P < 0.02 for linkage in both groups of families is 270 kb from EMX2. In three sibships, we found recessive linkage to KHDRBS3, previously reported in a Somali family. In another family we discovered sex‐reversal associated with VUR, implicating PRKX, for which there was weak support for dominant linkage in the overall data set. Several other candidate genes are suggested by our linkage or association results, and four of our linkage peaks are within copy‐number variants recently found to be associated with renal hypodysplasia. Undoubtedly there are many genes related to VUR. Our study gives support to some loci suggested by earlier studies as well as suggesting new ones, and provides numerous indications for further investigations.